The foot, Anatomy notes - Ferdinando Paternostro; Cristiana Veltro; Jacopo Junio Valerio Branca; Anna Vacca (Infermieristica Journal, 2022)
The foot has 28 bones, 30 joints, and more than 100 muscles, ligaments, and tendons. These structures work together to carry out two main functions: weight-bearing and propulsion. Plus, the foot must be flexible to adapt to uneven surfaces and remain stable. In this article, we briefly illustrate the anatomy of the foot and its various structures